Pelatihan Senam Hamil Pada Ibu Trimester III Di Desa Namasula - Erlin Kiriwenno; Oktovina Sofiah Rattu; Jumita Rumbia (Poltekkes Kemenkes Denpasar, 2019)
Women who are young pregnant will feel nauseous, vomiting, chills and weakness. This feeling of nausea and vomiting will decrease until the first trimester ends. In the second trimester the body has begun to adapt and the feeling of nausea and vomiting has begun to decrease. However, in the third trimester, complaints caused by enlargement of the stomach, anatomical changes and hormonal changes will cause the appearance of complaints in pregnant women. These complaints include lower back pain, shortness of breath, varicose veins, haemorrhoid, sleep disorders, diastasis recti, pelvic pain and others. One of the complaints of pregnant women is sleep disorders that are often experienced by pregnant women, even though the pregnancy is normal. Pregnancy exercise is a form of antenatal care. Pregnancy exercise has been shown to help change the body's metabolism during pregnancy. Pregnancy exercise will help heart function so that pregnant women will feel healthier and don't feel short of breath Exercise and relaxation techniques during pregnancy are needed to reduce anxiety for pregnant women. Pregnancy exercise is one of the sports activities that mothers can do during pregnancy. The benefits of pregnancy exercise include mental and physical preparation of pregnant women in order to achieve a physiological, natural and comfortable delivery, as well as strengthening the pelvic floor muscles to prepare for pushing and to achieve optimal relaxation during pregnancy to delivery, both physically and psychologically.Keywords: pregnancy exercise, pregnancy.